Hypertension and Renal Organ Damage - Pontremoli, Roberto (Practical Case Studies in Hypertension Management,, 2018)
This book guides readers through a wide spectrum of clinical presentations in patients with arterial hypertension and different degrees of renal impairment, ranging from asymptomatic urine abnormalities to end stage renal disease. On the basis of six case studies, the author reviews and discusses current guidelines and recommendations aimed at optimizing the diagnostic and therapeutic approach both to renal and cardiovascular risk in commonly encountered real-world clinical scenarios including challenging cases of diabetic kidney disease, ischemic nephropathy and resistant hypertension. It also explores anti-hypertensive drug combinations, including single or multiple RAAS-I, lipid lowering and antiplatelet drugs, as well as the appropriate use of glucose lowering drugs in the context of chronic kidney disease. This handy and practical book provides physicians in the area of general and internal medicine, as well as specialists in the cardiovascular, metabolic and renal fields valuable insights into optimal therapeutic targets for blood pressure and glucose control in renal patients.